THE INFLUENCE OF GIVING INCENTIVES AND THE APPLICATION OF WORK DISCIPLINE TO THE WORKING SATISFACTION OF PERMANENT EMPLOYEES IN THE OFFICE OF PAJARAKAN SUB DISTRICT, PROBOLINGGO - Hermanto Hermanto (International Journal of Social Science and Business, 2018)
This research intends to know and analyze the incentive and work discipline of its effect on employee job satisfaction in Pajarakan Sub-district, Probolinggo. the type of explanatory research is to find the influence or causal relationship between variables, the population of all employees in Pajarakan sub district with the technique of purposive sampling using inclusion criteria is permanent employees and those who are willing to be respondents as much as 20 people, the analysis of multiple linear regression with F test and t test as hypothesis test .The result of the study describes the incentive and work discipline has simultaneous influence to job satisfaction, and partially incentive variable has a significant and dominant influence on job satisfaction variable while work discipline variable partially have a positive but not significant influence on the variable of job satisfaction indicates the application of work discipline needs sufficient understanding and awareness. Performance indicators have the lowest correlation to incentives so that performance improvement should receive management attention and compliance indicator on the lowest correlate working standard to the work discipline so that management need to increase the attention and awareness in increasing the compliance to the standard work in fulfilling job satisfaction of employees in Pajarakan Sub-district Probolinggo.